INVESTIGATING TEACHING STRATEGY IN ENGLISH ONLINE LEARNING FOR ELEMENTARY STUDENTS - Zaidatus Sholihah; Oikurema Purwati; Tengsoe Tjahjono (JURNAL PENDIDIKAN GLASSER, 2023)
The study focused on investigating the teaching strategy used by an English teacher in teaching Elementary students through online learning. Teaching young learners needs creativity to keep the students active and enthusiastic about learning. Especially the condition required to conduct online learning. Teachers should keep the students motivated and understand the material easily. This study also elaborated on the challenges that the teacher faced during online learning. A qualitative method was used in this study. The data collection techniques are observation and interview. The data was gained from an elementary school in Surabaya. The observation was held in the first grade for twelve meetings. The result showed that the teacher used two learning models during online learning. It was synchronous and asynchronous learning. In synchronous learning, the teacher used Listen and Repeat, Listen and Do, Short Conversation, Question and Answer, Quiz and Sing and Move. Meanwhile, in Asynchronous learning, the teacher used three strategies. They were Role play, Daily Tests, and Video Blogs (Vlogs). Moreover, the teacher also admitted that she faced challenges during teaching through online learning. The challenges came from the teacher herself, the students, and the parents.